The Antecedents of Artificial Intelligence-induced Pedagogical Designing Technostress among International Science Educators: Latent Content Insights from Reddit Commentaries - Obmerga, Marwin; Caballes, Dennis (GILE Journal of Skills Development, 2026)
Artificial intelligence (AI) is rapidly advancing and increasingly embedded in education, provoking debates on its detrimental effects on teaching and learning, particularly within highly structured disciplines such as the sciences. This study examined the antecedents of Artificial Intelligence-induced Pedagogical Designing Technostress by analysing commentaries posted by science educators from diverse countries who actively engage in professional exchanges and discourses on Reddit. From a total of 210 datasets, collected through a meticulous Python- and Theoretical Framework-assisted data scraping process and verified manually for contextual integrity, the study employed Latent Content Analysis to chart the science educators-Redditors’ lived experiences across science-related subreddits. Three (3) themes emerged: Disruptions to Coherent Science Lesson Design, Uncertainties in Science Pedagogical Integration, and Pressures of Efficiency-Propelled Science Instruction. Theoretically, the inquiry extends conceptualisations of technostress by situating it at the intersection of AI and pedagogical designing, demonstrating how algorithmic mediation reshapes science educators’ epistemic and ethical responsibilities. Practically, it underscores the urgency to move beyond fragmented experimentation and develop structured institutional mechanisms and professional development pathways that equip science educators to critically appraise AI-generated content while preserving disciplinary autonomy.